Transcription of the JC virus archetype late genome: importance of the kappa B and the 23-base-pair motifs in late promoter activity in glial cells. - Mayreddy, R P (1996)
The transcription control region of the archetype strain of the human polyomavirus JC virus (JCV(Cy)), unlike its neurotropic counterpart (JCV(Mad-1)), contains only one copy of the 98-bp enhancer/promoter repeat with the 23-bp and the 66-bp insertion blocks. Early studies by us and others have indicated that the structural organization of JCV(Mad-1) is critical for glial cell-specific transcription of the viral genome. In addition, the kappa B regulatory motif found in the JCV(Mad-1) genome, which also exists in JCV(Cy), confers inducibility to the JCV(Mad-1) early and late promoters in response to extracellular stimuli. In this study, we have investigated the regulatory role of the 23- and the 66-bp blocks and their functional relationship to the kappa B motif in stimulating transcription of the Cy early and late promoters in glial cells. We demonstrate that mutations in the kappa B motif reduce the basal activity of the Cy early promoter and decrease the levels of its induction by phorbol myristate acetate or factors derived from activated T cells. Under similar circumstances, mutation in the kappa B motif completely abrogated the basal and the induced levels of transcription of the viral late promoter. Using deletion and hybrid promoter constructs, we have demonstrated that the 23-bp block of the Cy promoter plays a critical role in the observed inactivation of Cy late promoter transcription in glial cells. Results from DNA binding studies have indicated the formation of a common nucleoprotein complex with the 23-bp sequence, mutant kappa B (kappa B(mut)), and wild-type kappa B (kappa B(wt)). Analysis of this complex by UV cross-linking has identified a 40-kDa protein which binds to the 23-bp sequence and the kappa B motif. The importance of these findings for the activation of JCV(Cy) under various physiological conditions is discussed.